High precision studies of an intraplate earthquake sequence in northeast Brazil - Takeya, Mario Koechi (1992)
From May 1987 to April 1988, a 9 station, seismic network was operated near the town of João Câmara (533'S, 3551'W) in Rio Grande do Norte state, Brazil. The network was installed 6 months after the occurrence of a mb =5.1 earthquake. This thesis is concerned with the study of microearthquakes recorded by this network, which is in the Precambrian Borborema Province of northeast Brazilian shield. The study revealed a remarkably well-defined distribution of seismicity associated with a simple fault structure. Hypocentre location was done using the HYPO71 program. The results of the analysis show that the fault is divided into two main segments with the same N37E strike. The north segment is dipping 76NW. The south segment is more nearly vertical, dipping about 82NW and composed of three or more closely spaced almost parallel faults. A small gap and a low seismicity zone were found to separate the north and south segments. No events deeper than 9 km were found in the entire region studied. Examination of the epicentral map and corresponding vertical cross sections also revealed that events are not random but are clustered. Right lateral strike slip with a small normal component was inferred as the fault mechanism from composite fault plane solutions. Off-fault events distant from the main fault were also observed, their pattern showing a classical example explained by the model of Das & Scholz as a consequence of off-fault shear stress increase after the occurrence of the main earthquake. Magnitude determinations for the events recorded by the telemetric network have been performed by developing a specific earthquake magnitude scale based on the duration of the observed seismic signal. A maximum likelihood estimate of b-value shows no significant variation during the recording period. Shear wave splitting was observed in the J.Câmara region in all the selected events recorded by the three component station JCAZ. The polarization direction of the first split shear-wave arrival for those events lay in the north-south direction which does not agree with the premise of extensive dilatancy anisotropy for a maximum compressive stress in the east-west direction as inferred by the fault plane solutions.